Neo-populisms: Key hypotheses and types. The European Experience - Morlino, Leonardo (2022)
What happens when, after a resounding electoral victory, populist parties and their leaders become prime ministers or ministers in governments or participate in the decision-making process? To reply to such a question, first, the authors propose a simple distinction between two neo-populisms and then control if there is adaptive institutional responsiveness with a possible consequent improvement of social rights and lowering of inequalities. The main conclusion suggested by the empirical analysis is that revendicative and redistributive leaders and parties are more likely to succeed in economically weaker countries